2020
DOI: 10.1103/physrevlett.125.240401
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Delocalization via Emergent Symmetry

Abstract: Many-body localization (MBL) provides a mechanism to avoid thermalization in many-body quantum systems. Here, we show that an emergent symmetry can protect a state from MBL. Specifically, we propose a Z2 symmetric model with nonlocal interactions, which has an analytically known, SU(2) invariant, critical ground state. At large disorder strength all states at finite energy density are in a glassy MBL phase, while the lowest energy states are not. These do, however, localize when a perturbation destroys the eme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…For both the uniform δ = 0 and disordered δ = 3 system, the Rényi entropy follows Eq. (11). Without disorder, the fit y = 0.247x + 1.88 agrees with the expected slope C = 0.25.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…For both the uniform δ = 0 and disordered δ = 3 system, the Rényi entropy follows Eq. (11). Without disorder, the fit y = 0.247x + 1.88 agrees with the expected slope C = 0.25.…”
supporting
confidence: 70%
“…While emergent symmetry has previously been identified as a mechanism to obtain weak violation of MBL [11], we have here shown that weak violation of MBL can also happen without the presence of emergent symmetry. Specifically, we have constructed a model with a known eigenstate.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations